The influence of family function, social support, and infants’ health on mothers’ postnatal depression in three months after birth - Nurfurqoni, Fuadah Ashri; Hastuti, Dwi; Sunarti, Euis; Riany, Yulina Eva (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
In the postnatal period, mothers face the challenge of adjusting to new roles and responsibilities, which can lead to increased stress and a risk of developing postpartum depression. This study explores the relationship between maternal characteristics, family functioning, social support, infant health, and postpartum depression. Data were obtained through a Family Function (Fungsi-Ga) questionnaire, the Multidimensional Scale of Perceived Social Support (MSPSS), and the Edinburgh Postnatal Depression Scale (EPDS) from 150 mothers of three-month-old babies. The analysis was conducted using uses PLS-SEM (Partial Least Squares-Structural Equation Model). The research results show that the model of postnatal depression formed is fit (goodness of fit .252). Social support has direct (β= -.170) and indirect negative effects on postnatal depression through family functioning and babies’ health (β= -.186). The family function has a direct negative effect (β= -.395) and an indirect one through babies’ health on postnatal depression (β= -.280), while babies’ health has a negative effect on such depression (β= -.301). The results of the research imply that education for mothers on social support, family functioning, and how to care for newborns, which helps ensure that babies’ health is optimal, is critical in reducing the risk of postnatal depression, especially in the first three postnatal months.